Mechanical Transmission of Lumpy Skin Disease Virus by Stomoxys spp. (Stomoxys calsitrans, Stomoxys sitiens, Stomoxys indica), Diptera: Muscidae - Issimov, Arman (Animals (Basel), 2020)
SUMMARY: Lumpy skin disease (LSD) is an emerging disease in Kazakhstan, and currently the means of transmission is uncertain. In the current study, mechanical transmission of lumpy skin disease virus (LSDV) by Stomoxys species from infected to naive animals was demonstrated under laboratory conditions. Flies partially fed on LSDV-infected cattle were placed onto recipient animals within a 1 h time period to complete their feeding process. In addition to this, virus was isolated from all three Stomoxys species immediately and 6 h post feeding on LSDV infected animal, while virus DNA was detectable up to 48 h post-feeding by PCR. ABSTRACT: Samples collected for PCR from recipient animals tested positive in 5 out of 6 cases, while the virus was isolated from 4 of 6 animals. The clinical signs exhibited by recipient animals were mostly moderate in nature with only one severe case. To our knowledge, this is the first time that transmission of LSDV by three Stomoxys species has been demonstrated, and their role as mechanical vectors of LSDV is indicated.